The Relationship Between Waste Bank Utilization Behaviour & Domestic Waste Volume at the Household Level at Aur Village, Medan Maimun Sub-district - Siti Khairuni Taniah; Sri Malem Indirawati (TALENTA Publisher, Universitas Sumatera Utara, 2026)
Urban functional areas are currently facing waste and environmental problems due to increasing social and economic activities, urbanisation rates, and urban population growth. One effort to reduce household waste volume is the utilization of a waste bank. This research aims to analyze the relationship between waste bank utilization behaviour and the volume of domestic waste at the household level in Aur Village, Medan Maimun Sub-district in 2024. This type of research is an analytic survey with a cross-sectional design. The sample in this study amounted to 40 people using the total sampling technique. Data analysis method in 2 stages: univariate analysis with frequency counts and bivariate analysis with the chi-square test and Spearman's correlation, with a significance level of α = 5% (0.05). The results showed that there was a significant relationship between housewives' knowledge (p = 0.003) and housewives' attitude (p = 0.02) with the behaviour of using the waste bank. There was no significant relationship with a positive pattern between the utilization of waste bank and domestic waste volume (r = 0.069) and (p = 0.673). This research provides the government with information on the use of waste banks to improve the program's effectiveness in reducing waste in the community. Furthermore, Non-Governmental Organizations can continue to provide education to improve customers' knowledge and attitudes, particularly in the area of waste management.